Historical system of public green areas – untapped potential of towns – on the example of Ciechocinek - Balik, Katarzyna; Lisowska, Magdalena (Protection of Cultural Heritage, 2023)
Historic green spaces in towns cities, especially those that build up a system of public areas, play an extremely important role in shaping the spatial structure of a town. These systems, often designed by excellent planners, architects and urbanists, are very durable elements of urban layouts and to a large extent determine the development of a town. This article presents the results of research on green areas in Ciechocinek conducted by the authors, from 2017 to 2022, as part of the statutory activities of the National Institute of Cultural Heritage. First of all, the functioning of a homogeneous system of public green areas in Ciechocinek is demonstrated, which clearly defines the character and specifitown of the town, and constitutes its enormous potential. The history of its formation and development, its characteristic features and values were presented, the state of preservation and threats were discussed, and actions were proposed to make full use of its potential. It emphasises the need to plan activities not only at the scale of the objects, but also in relation to the whole system, as it is their belonging to a larger whole that defines their essence and value. Acknowledgements: We would like to thank the National Institute of Cultural Heritage, within the framework of whose activities it was possible to carry out research on historic green areas in Ciechocinek, and to Mr Wiktor Hibner for providing us with archival materials and very valuable comments. Authors' contribution: The contribution of the authors' work to both the research on green areas in Ciechocinek and the preparation of this article are equal.